2020
DOI: 10.1002/lio2.487
|View full text |Cite
|
Sign up to set email alerts
|

Subjective functional outcomes in oropharyngeal cancer treated with induction chemotherapy using the MD Anderson Symptom Inventory (MDASI)

Abstract: Objectives: Evaluate the use of induction chemotherapy (IC) in oropharyngeal cancer (OPC) and its impact on subjective functional outcomes using a validated MD Anderson Symptom Inventory-Head and Neck (MDASI-HN) survey tool. Methods: A single institution retrospective review of OPC patients who received IC, including reasons given for using IC, regimens employed, responses, and patientreported outcomes (PRO). The latter included pain, distress, dysphagia, xerostomia, and feeding tube placement and dependency. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 25 publications
(34 reference statements)
0
6
0
Order By: Relevance
“…In those with oropharyngeal cancer (OPC), Mott FE et al also found that the baseline of xerostomia was observed in 42% of patients before IC, and the probability of patients reporting xerostomia after IC decreased to 36%. 14 Although <10% of the total saliva amount is secreted by the minor glands, it is important in lubricating the oral cavity. 10,18 In OPC patients, the baseline of xerostomia may be caused by the destruction of the minor glands owing to OPC cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In those with oropharyngeal cancer (OPC), Mott FE et al also found that the baseline of xerostomia was observed in 42% of patients before IC, and the probability of patients reporting xerostomia after IC decreased to 36%. 14 Although <10% of the total saliva amount is secreted by the minor glands, it is important in lubricating the oral cavity. 10,18 In OPC patients, the baseline of xerostomia may be caused by the destruction of the minor glands owing to OPC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies regarding breast cancer have shown that chemotherapy may impair the submandibular gland (SMG), which produces two-thirds of the unstimulated saliva. 11,14 However, there was no prospective study to assess the prevalence of IC-related xerostomia in NPC patients. In light of this, this study aimed to investigate the prevalence and predictive factors of IC-related xerostomia for NPC patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were also found by Mott et al, where pain, xerostomia, and dysphagia all increased with combined radiochemotherapy. 42 Both radiotherapy and chemotherapy are toxic and can damage the normal oral physiological structure and function of the oral cavity, increasing the symptom burdens. Patients with higher NRS scores exhibited more serious symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…R/M HNSCC that is not treatable with surgical resection or definitive radiotherapy is treated with palliative systemic therapy that includes platinum-based chemotherapy, cetuximab, and/or immune checkpoint inhibitors (ICIs) with anti-programmed death 1 (PD-1) antibodies ( Figure 1 ). Conventional therapy for locally advanced HNSCC often results in permanent impairments in chewing, swallowing, and tasting, along with a dry mouth, feeding tube dependence, and aspiration pneumonia [ 20 , 21 ]. These adverse events for survivors, coupled with the poor outcomes for R/M HNSCC, demonstrate the need for novel therapies with less toxicity and more efficacy.…”
Section: Introductionmentioning
confidence: 99%